Transição energética e engajamento público em Moçambique - Pereira, Crescêncio; Gonçalves, Euclides; Forquilha, Salvador (Desafios para Moçambique 2022, 2022)
Este estudo mostrou que, para serem analiticamente mais produtivos, os conceitos de circulação global, como o de transição energética, precisam ser adaptados para dar conta de realidades específicas num mundo que, historicamente, tem produzido relações desiguais. No caso de Moçambique, a estratégia para a transição energética passa pela exploração do gás natural, mas esta abordagem tem como limitação as características da indústria extractiva que produz poucas oportunidades de desenvolvimento ao nível local e tem o potencial de produzir impactos ambientais e sociais nefastos. Pressupostos de noções como engajamento público ou participação pública devem também ter em conta os contextos onde são introduzidas, de forma inseri-las nas dinâmicas de poder local e capitalizá-las com as experiências positivas existentes. No caso de Moçambique, foi demonstrado que qualquer entendimento ou estratégia para um engajamento público para uma transição energética deve considerar os níveis de abertura do espaço cívico, das capacidades dos cidadãos e das organizações da sociedade civil, e de pobreza energética nas regiões de extracção de recursos naturais. Em regiões como o Norte de Moçambique, onde níveis baixos de cobertura da rede de energia eléctrica se combinam com múltiplas formas de pobreza, os cidadãos colocam os problemas associados à transição energética em segundo plano em favor das necessidades relativas ao desenvolvimento local. Este estudo sobre transição energética e engajamento público em Moçambique mostrou os desafios que os intervenientes do subsector do petróleo e gás têm para mobilizar e expandir o espaço de debate público sobre formas de avançar no processo de transição energética em Moçambique. Da experiência de engajamento público existente, identificámos os três principais espaços de interacção ao nível internacional, nacional/central e ao nível local. Estes espaços de engajamento seguem dinâmicas mais ou menos autónomas e com poucas interligações. Experiências de engajamento público de Moçambique e outras partes do mundo mostram que as estratégias com maior nível de sucesso reconhecem a necessidade de articulação entre o Governo, as organizações da sociedade civil e a responsabilidade social das empresas para garantir o envolvimento das comunidades, além das convencionais consultas que são realizadas em exercícios para a mitigação dos impactos dos projectos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; natural resources / recursos naturais; politics / política

Could Mozambique become a hydrogen hub? - Hanlon, Joseph (Mozambique News Reports & Clippings, 2021)
The proposal for the Mphanda Nkuwa dam 60 km downstream from Cahora Bassa, and using the same water to generate more electricity, is back on the table. The dam has been proposed since the colonial era, but there has never been a market for the electricity. Producing hydrogen would be the perfect market. In this special issue, we look at Mphanda Kkuwa and the potential for hydrogen.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GP - Tete; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

Vale moves to exit coal business - Argus Media (2021)
In its first step to exit the coal business, Brazilian mining firm Vale will acquire all stakes held by Japanese trading house Mitsui in the Moatize coal mine and Nacala corridor coal infrastructure in Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Mozambique: Syrah Resources resumes graphite mining ahead of schedule after year's stoppage (Mozambique, 2021)
Australian mining company Syrah Resources has resumed production of graphite ahead of schedule at its Balama mine in Cabo Delgado, northern Mozambique, it said in a statement to shareholders on Tuesday. The plant's activities were halted in late March last year following the country's implementat
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; private sector / setor privado

Altona Rare Earths soars as it enters MoU to acquire rare earths project (Vox Markets, 2021)
Shares in Altona Rare Earths soared by over 60% today following the news that the group has entered into an MoU to acquire up to 70% in the Monte Muambe Rare Earths Project. Should it choose to proceed with the investment following a 90-day due diligence period, the project would represent its first venture into a carbonatite hosted REE asset.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Economia Política da Governação de Recursos Naturais em Nampula - Salimo, Padil (Akilizetho – ADS, 2020)
A Akilizetho-ADS elaborou um estudo denominado Economia Política da Governação dos Recursos Naturais, em Nampula. A pesquisa foi feita entre Dezembro de 2019 e Janeiro de 2020. A abordagem do estudo foi baseada numa análise de economia política e circunscrito apenas aos recursos minerais e hidrocarbonetos. O objectivo do estudo foi de compreender as relações entre governos, empresas extractivas, comunidades, sociedade civil e reflectir sobre as dinâmicas de governação da indústria extractiva e suas implicações sobre os direitos das comunidades afectadas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; natural resources / recursos naturais

The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

The politics of domestic gas: The Sasol natural gas deals in Mozambique - Salimo, Padil; Buur, Lars; Macuane, Jose Jaime (The Extractive Industries and Society, 2020)
This article explores the ways in which the ruling Frelimo elite in Mozambique engaged creatively with the opportunities and constraints created by Sasol's Pande and Temane natural gas project as they have evolved from the early 2000s until today. This is a period that has seen ruling-elite actors become involved in various projects related to the production of electricity from ‘domestic natural gas’. We argue that focusing on the initial gas investment and how it evolved over time makes it possible to understand the dynamics related to deal-making during the formative years when the Mozambican petroleum industry was reformed by separating its commercial and regulatory functions. More specifically we explore how access to revenues and rents related to natural gas projects have evolved. We point out that, although the Pande-Temane gas project has increased revenue generation, most of the gas was sold to the South African major, Sasol, for a very low amount of revenue during the first phase of the project. Revenues from the second phase, starting in 2012, did not increase dramatically, even though Mozambique acquired access to 50% of the gas from the extension of the pipeline and increased production. Instead, the increase in domestic gas allocated to the Mozambican market involved the allocation and distribution of gas to private companies at special prices, most of which were controlled by dominant ruling-elite factions under the Chissano and Guebuza governments. We argue that this has been the main mechanism for the transfer of rents from the public to the private domain.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Natural resources, institutions, and economic transformation in Mozambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
In the light of Mozambique’s natural resources boom—especially its large-scale investments in mining, oil, and gas—this paper analyses the prospects for the extractive industries to contribute to economic transformation from an institutional perspective. To this purpose, we address the institutional dynamics of the resources sector and consider the underlying causes of the identified outcomes. The National Development Strategy, as the instrument presenting the vision for economic transformation and diversification, is discussed. The paper is based on a desk review—documental and bibliographic—and on primary data gathered by the authors as part of their research into the field of natural resources and the political economy of development. We conclude that, given Mozambique’s political patronage and clientelism, intra-ruling elite competition, limited productive base, weak state capacity, high level of poverty, and recurrent fiscal deficits, the prospects of the current resource boom leading to economic transformation, despite its considerable potential, are at best uncertain.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Recursos naturais, instituições e transformação económica em Moçambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
Face ao boom de recursos naturais em Moçambique — em especial dos seus grandes investimentos em exploração mineira, petróleo e gás —, este documento analisa a perspectiva de as indústrias extractivas contribuírem para a transformação económica de um ponto de vista institucional. Para esse efeito, abordamos a dinâmica institucional do sector dos recursos e consideramos as causas subjacentes aos resultados identificados. É discutida a Estratégia Nacional de Desenvolvimento enquanto instrumento que apresenta a visão para a transformação e diversificação económica. O documento baseia-se numa revisão documental e bibliográfica e em dados primários recolhidos pelos autores no âmbito da sua investigação no campo dos recursos naturais e da economia política do desenvolvimento. Concluímos que, dado o patrocínio político e o clientelismo de Moçambique, a competição no interior da elite governante, a base produtiva limitada, a fraca capacidade do Estado, o elevado nível de pobreza e os défices fiscais recorrentes, as perspectivas de que o actual boom de recursos leve à transformação económica, apesar do seu considerável potencial, são, na melhor das hipóteses, incertas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - Invest in the Energy Sector of Mozambique - African Oil and Power (Africa Oil and Power, 2020)
Since initial exploratory drilling in 2007 by U.S. operator Anadarko, Mozambique has uncovered vast natural gas volumes within its offshore basins, and now carries the potential to be the fourth largest natural gas exporter globally. With discoveries ranging from Anadarko’s initial 480 feet of gas found in Area 1 in 2010, to Eni’s discovery of 425 billion cubic meters one year later, the onus now lies on major operators including Royal Dutch Shell, Total, Eni and more to develop the requisite infrastructure to exploit the reserves, generate exports and bring revenue into the country. Potential inhibitors to the development of such resources include two ‘black swan’ events that have occurred since early-2020. In addition to the onset of COVID-19 in March – including a specific outbreak on Total’s Mozambique LNG development – the gas-rich Cabo Delgado province is facing a growing Islamist insurgency that began in the country in 2017. Nevertheless, the world-class nature of Mozambique’s gas assets has offset such inhibitors, and the country recently secured the largest foreign direct investment in Africa to date through its Mozambique LNG development. Gas monetization projects push forward on schedule, as the nation continues on its path to becoming a global energy giant.
Keywords: G - Mozambique / Moçambique; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

Finanças Internacionais e Formação do Capitalismo Nacional em Moçambique - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2020, 2020)
Este capítulo descreve e explica como e por que razão a economia moçambicana e as suas dinâmicas de expansão e de crise, as suas contradições e os seus paradoxos foram estruturados e articulados pela sua relação de dependência com o capital financeiro privado internacional, e as implicações desta relação para as características, as dinâmicas e as opções de acumulação privada de capital e de desenvolvimento da sociedade como um todo em Moçambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; natural resources / recursos naturais; private sector / setor privado